Pengaruh Back Exercise Terhadap Keluhan Low Back Pain (LBP) pada Pekerja Area Sorting di TPA Talang Gulo Kota Jambi - Afifah Kurnia Dewita; Rumita Ena Sari; Willia Novita Eka Rini; David Kusmawan; Oka Lesmana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Low back pain is the most common musculoskeletal disorder experienced by workers, one of which is sorting workers. Back exercise is useful for strengthening the abdominal and back muscles so that the body is physiologically upright. This study aimed to determine the effect of back exercise on complaints of low back pain in TPA Talang Gulo sorting workers, in Jambi City. This type of research was a quantitative study with a quasi-experimental method. The research population was the Talang Gulo landfill sorting workers with a sample of 34 people. Data collection used questionnaires and visual analogue scale (VAS) pain scale sheets. The results of data analysis used the chi-square test to show that there was no relationship between age (p=0.363>0.05), gender (p=0.202>0.05), years of service (p=0.1000>0.05), and BMI (p=0.1000>0.05). Then, there is a relationship between exercise habits (p= 0.004<0.05), workload (p= 0.021<0.05), repetition (p =0.029<0.05), and work attitude (p = 0.010<0.05). On complaints of low back pain in sorting workers at TPA Talang Gulo. The paired sample t-test data analysis shows an effect of back exercise on complaints of low back pain (p=0.000 <0.021).There is a relationship between exercise habits, workload, repetition, and work attitude with complaints of lower back pain, and back exercise exercises affect complaints of low back pain in Talang Gulo TPA Sorting workers.Sorting workers exercise at least 3 times a week to reduce complaints of low back pain, apply good work attitudes such as not slouching and stretching while working on their hands and waist.